Higher rates of bleeding and use of treatment products among young boys compared to girls with von Willebrand disease. Issue 1 (29th October 2019) - Abe, Karon; Dupervil, Brandi; O'Brien, Sarah H.; Oakley, Meredith; Kulkarni, Roshni; Gill, Joan Cox; Byams, Vanessa; Soucie, Michael J.
Abstract: There are limited observational studies among children diagnosed with von Willebrand Disease (VWD). We analyzed differences in bleeding characteristics by sex and type of VWD using the largest reported surveillance database of children with VWD (n = 2712), ages 2 to 12 years old. We found that the mean ages of first bleed and diagnosis were lowest among children with type 3 VWD. It was even lower among boys than girls among all VWD types, with statistically significant difference among children with type 1 or type 3 VWD. Children with type 3 VWD also reported higher proportions of ever having a bleed compared to other VWD types, with statistically higher proportions of boys compared to girls reporting ever having a bleed with type 1 and type 2 VWD. A similar pattern was observed with the use of treatment product, showing higher usage among type 3 VWD, and among boys than girls with type 1 and type 2 VWD. While there were no differences in life quality or in well‐being status by sex, children with type 3 VWD showed a greater need for mobility assistance compared to children with type 1 and type 2 VWD. In an adjusted analysis among children with type 1 VWD, boys showed a significant association of ever bleeding [hazard ratio 1.4; P ‐value <.001)] compared to girls. Understanding phenotypic bleeding characteristics, well‐being status, treatment, and higher risk groups for bleeding among pre‐adolescent children with VWD will aid physicians in efforts to educate families about bleeding symptoms.